Testing of Bleaching Application on Kingwood (Dalbergia cearensis Ducke) Wood - Hüseyin Peker; Ümit Ayata (Drvna Industrija)
In this study, surface changes (whiteness index: WI*, color parameters, and glossiness properties) occurring after bleaching with oxalic acid (C2H2O4) and hydrogen peroxide (H2O2) + sodium hydroxide (NaOH) chemicals in kingwood (Dalbergia cearensis Ducke) wood, used for high-quality applications such as quality turning, marquetry, furniture, inlay work, musical instruments, and decorative items, were investigated. The ΔE* values were determined as 5.46 for the single component and 8.69 for the double component. Decreases in L* and ho parameters were obtained by the action of the C2H2O4 chemical, while increases were observed in the a*, C*,and b* parameters. Additionally, the use of H2O2 + NaOH chemicals in the bleaching process resulted in increases in L*, b*, C*, and ho values, with a decrease noted in the a* parameter. Observations revealed reductions in glossiness values at 60 and 85 degrees when employing two distinct bleaching agents in both orientations. It can be said that the bleaching agents used in the study exert varying effects as modifiers on the surface of wooden materials.